The Meaning of Survival in the Poetry of Jacob Isaac, and its Semantics Learning Implementation - Hertin Indira Utojo; Oom Rohmah Syamsudin (INFERENCE: Journal of English Language Teaching, 2022)
The social, political, and economy atmosphere of a country often evokes the desire of literary activists to express their imagination, feelings, ideology in the form of social, political and cultural criticism through art, including poetry. Likewise, Jacob Isaac, a Bachelor and Master of Arts, as well as Doctor of English Literature, who was born in Kerala, South India, expresses imagination, feelings, ideology by creating the English poetry. In this research, the research writer chose three poetry written by Jacob Isaac as data sources entitled Indifference, Neural Mapping, Aging Liberty. The objective of this research is to describe the meaning of (1) survival in the above poetry; and (2) its implementation in English semantics learning. The research writer uses a qualitative research method and triadic semiotic model of Charles Sanders Peirce, consists of (1) representamen consists of rhyme form and sound, syntactic, semantic, pragmatic relates to deixis, figurative and isotopy aspects); (2) interpretant consists of the biography of Jacob Isaac, history of India, social, political and cultural background aspects). The goal using interpretant is in order to get the research results more objective. This research was conducted from March to May 2021.